Advances in Conceptual Electronic Nanodevices based on 0D and 1D Nanomaterials - Zhang, Yafei; Duan, Li Franklin; Zhang, Yaozhong; Wang, Jian; Geng, Huijuan; Zhang, Qing (Nano-Micro Letters, 2013)
Nanoelectronic devices are being extensively developed in these years with a large variety of potential applications. In this article, some recent developments in nanoelectronic devices, including their principles, structures and potential applications are reviewed. As nanodevices work in nanometer dimensions, they consume much less power and function much faster than conventional microelectronic devices. Nanoelectronic devices can operate in different principles so that they can be further grouped into field emission devices, molecular devices, quantum devices, etc. Nanodevices can function as sensors, diodes, transistors, photovoltaic and light emitting devices, etc. Recent advances in both theoretical simulation and fabrication technologies expedite the development process from device design to prototype demonstration. Practical applications with a great market value from nanoelectronic devices are expected in near future.